Efficient Hydrogen Liberation from Formic Acid Catalyzed by a Well‐Defined Iron Pincer Complex under Mild Conditions. Issue 25 (6th May 2013) - Zell, Thomas; Butschke, Burkhard; Ben‐David, Yehoshoa; Milstein, David
<x xml:space="preserve">Abstract</x> Hydrogen liberation: An attractive approach to reversible hydrogen storage applications is based on the decomposition of formic acid. The efficient and selective hydrogen liberation from formic acid is catalyzed by an iron pincer complex in the presence of trialkylamine (see scheme). Turnover frequencies up to 836 h−1 and turnover numbers up to 100 000 were achieved at 40 °C. A mechanism including well‐defined intermediates is suggested on the basis of experimental and computational data.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>